Lymphoblastoid and Jurkat cell lines are useful surrogate in developing a CRISPR-Cas9 method to correct leukocyte adhesion deficiency genomic defect - Ramadan, Ahmad R.; Ben Khalaf, Noureddine; Trabelsi, Khaled; Bakheit, Halla; Ben-Mustapha, Imen; Barbouche, Mohamed-Ridha; Fathallah, M-Dahmani (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction: Leukocyte adhesion deficiency type 1 (LAD1) is a severe inborn error of immunity caused by mutations in the ITGB2 gene, which encodes the beta-2 integrin subunit (CD18). These mutations lead to the absence or deficiency of CD18/CD11a, b, and c heterodimers, crucial for leukocyte adhesion and immune function. CRISPR-Cas9 Gene editing technology represents a promising approach for correcting these genomic defects restore the stable expression of CD18 and reverse the disease.Methods: We developed a CRISPR-Cas9-based gene correction strategy using Jurkat cells and patient-derived lymphoblastoid cell lines as surrogates for hematopoietic progenitor cells. Three candidate gRNAs were first predicted in silico using CRISPOR and experimentally tested in wild-type ITGB2-expressing Jurkat cells to identify the gRNA with the highest genomic DNA cleavage efficiency. The most efficient gRNA was then paired with espCas9 and used alongside five homology-directed repair templates (HDRs) (single-stranded donor oligonucleotides, ssODNs) to repair ITGB2 defects in patient-derived lymphoblastoid cell lines. CD18 expression levels in edited cells were quantified via flow cytometry, and whole-genome sequencing (WGS) was conducted to assess off-target effects and insertion accuracy.Results: Among the three candidate gRNAs, 2-rev gRNA exhibited the highest genomic cleavage rate in Jurkat cells. Using this gRNA with espCas9 and HDR-2, we achieved a 23% restoration of CD18 expression in LAD1 patient-derived cells, a level sufficient to change the disease course from severe to moderate. Whole-genome sequencing confirmed the absence of off-target mutations or undesired DNA insertions, demonstrating high specificity and precision in gene correction.Discussion: This CRISPR-Cas9-based method provides a precise and effective approach for correcting ITGB2 mutations in LAD1 patients. The high-fidelity gene editing process, validated through WGS, supports its potential for future applications in CD34+ hematopoietic stem cell therapies. The approach can be further optimized for clinical translation, offering a path toward a stable and long-term cure for LAD1.